1978
DOI: 10.1109/tit.1978.1055892
|View full text |Cite
|
Sign up to set email alerts
|

Broadcast channels with confidential messages

Abstract: Absrfucr-Given two discrete memoryless channels @MC's) with a common input, it is desired to transmit private messagea to receiver 1 at r&R, andcommon meswgea to both receivers at rate R,, while keeping receiver 2 as ignorant of tbe private messages as possible. Measurhg ignorance by equivocation, a single-letter characterization is given of the. achievable trfplea (RI&R,-,) where 4 is the equivocation rate. Based on this channel ding result, the related source-channel matdng problem is also settled. l%ese res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
3,207
3
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 3,106 publications
(3,285 citation statements)
references
References 6 publications
33
3,207
3
1
Order By: Relevance
“…A fundamental problem is the generation of a mutual key about which an adversary has virtually no information. Wyner [18] and later Csiszár and Körner [10] considered the natural message-transmission scenarios in which the legitimate partners Alice and Bob, as well as the adversary Eve, are connected by noisy channels. In Csiszár and Körner's setting, Alice sends information (given by the random variable X) to Bob (receiving Y ) and to the opponent Eve (who obtains Z) over a noisy broadcast channel characterized by the conditional distribution P Y Z|X .…”
Section: Models Of Information-theoretic Secret-key Agreementmentioning
confidence: 99%
“…A fundamental problem is the generation of a mutual key about which an adversary has virtually no information. Wyner [18] and later Csiszár and Körner [10] considered the natural message-transmission scenarios in which the legitimate partners Alice and Bob, as well as the adversary Eve, are connected by noisy channels. In Csiszár and Körner's setting, Alice sends information (given by the random variable X) to Bob (receiving Y ) and to the opponent Eve (who obtains Z) over a noisy broadcast channel characterized by the conditional distribution P Y Z|X .…”
Section: Models Of Information-theoretic Secret-key Agreementmentioning
confidence: 99%
“…As mentioned in the introduction, Theorem 1 has already been known to hold for general (not necessarily efficient) protocols [3,1].…”
Section: A General Expression For the One-way Secret-key Ratementioning
confidence: 96%
“…For one-way communication, it is already implied by a result in [3] and has later been shown in [1] that the secret-key rate S → (X; Y |Z) is given by the supremum of H(U |ZV ) − H(U |Y V ), taken over all possible random variables U and V obtained from X. 1 However, as this is a purely information-theoretic result, it does not directly imply that there exists an efficient key-agreement protocol.…”
Section: Secret-key Agreementmentioning
confidence: 97%
See 1 more Smart Citation
“…After that, Wyner [5] and Csiszár and Körner [6] showed that it is possible to securely communicate between Alice and Bob, under the assumption of the presence of noise in communication channels from Alice to Bob, and to an adversary Eve. By taking various assumptions on the adversary's ability, many applications have been derived in the field of physical layer security.…”
Section: Related Workmentioning
confidence: 99%